Effects of cryopreservation on the mitochondrial bioenergetics of bovine sperm. Issue 1 (30th September 2022) - Algieri, Cristina; Blanco‐Prieto, Olga; Llavanera, Marc; Yeste, Marc; Spinaci, Marcella; Mari, Gaetano; Bucci, Diego; Nesci, Salvatore
Abstract: This study evaluated the bioenergetic map of mitochondria metabolism in cryopreserved bovine sperm. The detected oligomycin‐sensitive basal respiration supported ATP production; frozen–thawed spermatozoa were found to have a coupling efficiency higher than 0.80. Cell respiration, however, was not stimulated by the protonophoric action of FCCP, as its titration with 1, 2, 4 and 6 μM did not stimulate the uncoupling activity on oxidative phosphorylation as highlighted by unresponsive oxygen consumption. The unusual effect on the stimulation of maximal respiration was not related to fibronectin‐ or PDL‐coated plates used for cellular metabolism analysis. Conversely, irradiation of frozen–thawed bovine sperm with the red light improved mitochondrial parameters. In effect, the maximal respiration of red‐light‐stimulated sperm in PDL‐coated plates was higher than the non‐irradiated. In spite of this, red‐light irradiation had no impact on membrane integrity and mitochondrial activity evaluated by epifluorescence microscopy.